A parametric study of steel-concrete composite beams with hollow core slabs and concrete topping. (December 2020) - Ferreira, Felipe Piana Vendramell; Martins, Carlos Humberto; De Nardin, Silvana
Abstract: The use of industrialized elements results in the speed of execution, it avoids waste of materials, and it meets sustainability requirements. The steel profiles and hollow core slabs are included in this scope. The hollow core slab presents superior quality than cast in-situ structural elements, and it is produced in specific environments with technological control and monitoring. In general, a concrete topping is made for smooth and uniform finishing. Studies addressing the structural behavior of steel-concrete composite beams with hollow core slabs with concrete topping are scarce. The present work aims to investigate the behavior of steel-concrete composite beams with hollow core slabs with concrete topping, considering full and partial interaction. Geometric nonlinear analyses are performed based on experimental tests. The steel-concrete composite beams with hollow core slabs with concrete topping are simply supported and subjected to two points loads symmetrically spaced. The influence of concrete topping (50 mm of thickness), the in situ concrete strength (25 MPa, 30 MPa and 40 MPa), the transverse reinforcement diameter (10 mm, 12.5 mm and 16 mm), the interaction degree (shear connectors spaced at 120 mm, 175 mm and 225 mm), and the steel cross section (W360 × 51, W460 × 74 and W530 × 72) are the parameters investigated. The results are discussed, considering these parameters. It was concluded that the concrete topping increased the strength of the composite beams with precast hollow core slabs, the lower the degree of interaction, the greater the ductile behavior of the composite element as a whole. The in-situ infill concrete strength was directly influenced by the steel cross-sectional area, transverse reinforcement rate and interaction degree. The resistance of steel-concrete composite beams with precast hollow core slabs may vary depending on the transverse reinforcement rate and interaction degree. Ductile behavior was observed for all situations, considering partial interaction.